Artikel Pengaruh Ekstrakurikuler Tarung Derajat Terhadap Kecemasan Sosial Siswa SMA - Lutpi Nurhakim; Sufyar Mudjianto; Carsiwan Carsiwan (Jurnal Sporta Saintika, 2026)
Physical education in schools not only plays a role in improving students’ physical fitness and motor skills but also contributes to their psychological development, including social anxiety. Social anxiety can hinder interaction, self-confidence, and students’ participation in learning activities. Martial arts extracurricular activities such as Tarung Derajat are believed to provide a medium for mental development through physical training, discipline, structured social interaction, and experiences of achievement in group activities. This study aimed to analyze the effect of Tarung Derajat extracurricular participation on students’ social anxiety SMA. The study employed a pre-experimental method with a one-group pretest–posttest design. The research subjects consisted of 54 students participating in the Tarung Derajat extracurricular program. The instrument used was a Likert-scale social anxiety questionnaire that had met validity and reliability requirements. Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, and paired sample t-test with a significance level of α = 0.05. The results showed a significant difference between students’ social anxiety scores before and after participating in the training program (p < 0.05). Social anxiety scores decreased after training with an effect size greater than 0.80 (large category). It is concluded that Tarung Derajat extracurricular training significantly reduces students’ social anxiety and is recommended as a school-based non-academic developmental activity.